Heat retention of a photovoltaic/thermal collector with PCM. (August 2016) - Browne, Maria C.; Norton, Brian; McCormack, Sarah J.
Highlights: This study investigates the experimental thermal performance of a PV/T/PCM system. The thermophysical properties of the PCM eutectic, capric:palmitic acid, were found. The thermal behaviour of a PV/T/PCM system is compared to three reference systems. A PV/T/PCM system extended the amount of time for which the heat was available. The temperature of the water in the system with PCM was higher than that without PCM. Abstract: A novel PV/T/PCM system that generates electricity, stores heat and pre-heats water was characterised under outdoor conditions in Dublin, Ireland. The system design combines a PV module with a thermal collector; in which heat is removed from a heat exchanger embedded in PCM through a thermosyphon flow. System performance was compared against (a) the same system without PCM, (b) the same system without heat exchanger or PCM, and (c) the PV module alone. It was shown that the temperature attained by the water was approximately 5.5 °C higher when compared to a PV/T system with no PCM. PCM are shown to be an effective means of storing heat for later heat removal in a PV/T system.